(3Qbe GdMdd aj fXe GdOhds - (3CHh YHO Gddg dSGf GdOjf eMeO Hf YHO Gddg Hf SYjO GHf GdNWjH GdZQfGWi GdCfOdSj,J (B776 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi dG jfcQg ef SQMJ ai GdcGFfGJ acQg s
(3BNQgG (B:s
(3jgOjg eG GfbTY GdVdGd eGcQJ GdHcQ hGdCUGd heG gaG GdHQb heGL GdBd heGgei GdefSLe GdgWGd s
(3GfXQ HQbe (B" 1075" (3JGQjNs
(3fSNI KGfjIs
(3hgh efXheI ai SjQI GdQShd hGdNdaGA GdQGTOjf hHfi CejI hedhc Hfi fUQ HGdCfOdSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B235s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B262 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B372 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B206 s
Keywords: (3GdJGQjNs